2021
DOI: 10.1021/acsomega.1c04535
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Gas Chromatographic and Mass Spectrometric Characterization of Lipid-Rich Biological Matrices─Application to Human Cerumen (Earwax)

Abstract: Earwax is a readily accessible biological matrix that has the potential to be used in disease diagnostics. However, its semisolid nature and high chemical complexity have hampered efforts to investigate its potential to reveal disease markers. This is because more conventional methods of analysis such as gas chromatography–mass spectrometry (GC–MS) and liquid chromatography–mass spectrometry yield unsatisfactory results due to the presence of many nonvolatile and/or coeluting compounds, which in some cases hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 53 publications
3
12
0
Order By: Relevance
“…With the exception of compounds represented by peak numbers 1, 2, 5, 12, 13, 15, and 18, all of the listed compounds were also observed in the previous study reported in ref .…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…With the exception of compounds represented by peak numbers 1, 2, 5, 12, 13, 15, and 18, all of the listed compounds were also observed in the previous study reported in ref .…”
Section: Resultssupporting
confidence: 78%
“…Although each of the non-Ménière’s disease samples in Figure panels A through F were visually distinct, there were a subset of peaks representing compounds that they had in common. These, which were detected and identified in this work and earlier studies, include hexadecanoic acid, cis -9-hexadecenoic acid, cis -10-heptadecenoic acid, octadecanoic acid, cis -9-octadecenoic acid, squalene, cholesta-3,5-diene, and lanosterol . The chemical distinctions between these samples may be a consequence of differences in diet, lifestyle, age, or even the presence of medications consumed by the individual.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations